2010
DOI: 10.1007/s10439-010-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Loadings on Pectoral Pacemaker Implants: Correlation of In-line and Transverse Force of the Pectoralis major

Abstract: Recently we presented a method for the assessment of in vivo forces on pectoral device implants motivated from technological and clinical advancements toward smaller implantable cardiac pacemakers and the altered structural demands arising from the reduced device size. Objective of this study was the investigation of the intra-species proportionality of in-line force and transverse reaction force of the Pectoralis major for the characterization of mechanical in vivo loadings on pectoral implants. Two Chacma ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 20 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Secondly, the effects of load rate and fibre orientation on the viscoelastic behaviour of passive muscle under compression (Van Loocke et al, 2008) can be neglected since, in our experiments, the muscle was active with increased stiffness compared to passive state and the compression acted in cross-fibre direction with lower stiffness and viscosity compared to the fibre direction. The muscle contraction was sustained for approximately 0.5 s only (de Vaal et al, 2010a) and the compression rate was similar to that for the contraction of a relaxed muscle to a maximum level of 200 s À 1 (Wilkie, 1949). This value was considerably higher than the rate reported by Van Loocke et al (2008) for which they reported that the reaction of passive muscle to compression was devoid of viscous effects for instantaneous loadings.…”
Section: Simplified Model Of Sub-muscular Pectoral Implantmentioning
confidence: 74%
See 4 more Smart Citations
“…Secondly, the effects of load rate and fibre orientation on the viscoelastic behaviour of passive muscle under compression (Van Loocke et al, 2008) can be neglected since, in our experiments, the muscle was active with increased stiffness compared to passive state and the compression acted in cross-fibre direction with lower stiffness and viscosity compared to the fibre direction. The muscle contraction was sustained for approximately 0.5 s only (de Vaal et al, 2010a) and the compression rate was similar to that for the contraction of a relaxed muscle to a maximum level of 200 s À 1 (Wilkie, 1949). This value was considerably higher than the rate reported by Van Loocke et al (2008) for which they reported that the reaction of passive muscle to compression was devoid of viscous effects for instantaneous loadings.…”
Section: Simplified Model Of Sub-muscular Pectoral Implantmentioning
confidence: 74%
“…After conclusion of a related study (de Vaal et al, 2010a), two Chacma baboons (M b ¼23.9 7 1.2 kg) with pectoral sub-muscular implants of instrumented pacemakers (IPM) underwent imaging of the thoracic region with computed tomography (Aquilion 4, Toshiba Medical Systems, Zoetermeer, Netherlands) within two hours of euthanisation. Subsequently, the Pmajor was dissected and morphometric details were recorded as described by de Vaal et al (2010a): length along the estimated line of action L m , thickness and width at the crossbar of the buckle force transducer t m,cb and w m,cb and width over the IPM implant w m .…”
Section: Assessment Of Pectoral Anatomy In Baboon and Humanmentioning
confidence: 99%
See 3 more Smart Citations